Determination of Gallium in Red Mud after its Separation with β-Diketo Liquid Chelating Exchanger. - MONDAL, BANDANA; S. BHATIACHARYYA, SHUVENDU; DAS, A.K.; BALRAM, V. (Asian Journal of Chemistry, 2010)
A selective and quantitative method for the extraction of gallium(III) in methyl isobutylketone medium using a β-diketo liquid chelating exchanger is described. The conditions of separation of gallium i.e., pH, solvent, kinetics of extraction and the effects of various ions have been studied. The method has been applied successfully for the determination of gallium in red mud samples. To evaluate the accuracy of the method, the results were also checked with ICP–MS. Spiked recovery (98.2–101.5%) of gallium in red mud samples was also investigated.